A REVIEW AND CRITIQUE OF COMMANDER THEORY - Kim, Il-woon; James, Phillip C. (International Journal of Accounting & Finance Review, 2021)
The development of accounting was marked by three key theories namely: the proprietary theory, the entity theory and the fund theory. The commander theory was subsequently introduced to address the criticisms of the previous theories. This paper, therefore, outlines the history and development of the commander theory, it also outlines the essence of the theory and discusses general criticisms levied against it.  Despite some apparent weaknesses of the commander theory, one of which is that it is in-ward focused, there-by ignoring those outside the firm, it is simultaneously argued that the commander theory should be viewed as a significant theoretical framework in the formulation of accounting standards.JEL Classification Codes: M41.